Oxalate nephropathy and chronic turmeric supplementation: a case report - Onica Washington; Emily Robinson; Deetu Simh; Hemant Magoo; Ashish Verma; Helmut Rennke; Reza Zonozi (Brazilian Journal of Nephrology, 2024)
ABSTRACT We present a case of a 69-year-old man who presented for routine check-up and was incidentally found to have kidney failure with an initially unrevealing history and bland urinary sediment. He was diagnosed with oxalate nephropathy in the setting of chronic turmeric supplementation and chronic antibiotic therapy with associated diarrhea. Our case provides several key insights into oxalate nephropathy. First, the diagnosis requires a high index of clinical suspicion. It is uncommonly suspected clinically unless there is an obvious clue in the history such as Roux-en-Y gastric bypass or ethylene glycol poisoning. Diagnosis can be confirmed by histopathologic findings and corroborated by serum levels of oxalate and 24-hour urinary excretion. Second, the diagnosis can often be missed by the pathologist because of the characteristics of the crystals unless the renal pathologist has made it a rule to examine routinely all H&E sections under polarized light. This must be done on H&E, as the other stains dissolve the crystals. Third, one oxalate crystal in a routine needle biopsy is considered pathologic and potentially contributing to the AKI or to the CKD in an important way. Fourth, secondary oxalosis can be largely mitigated or prevented in many cases, especially iatrogenic cases. This can come through the surgeon or the gastroenterologist providing proper instructions to patients on an oxalate-restricted diet or other specific dietary measures. Lastly, this case highlights the success that results from cooperation and communication between the pathologist and the treating physician.